Modelling behaviour of cyber-physical system and verifying its safety based on algebra of event. (2018) - Tuo, Mingfu; Zhou, Cheng; Yin, Zhonghai; Zhao, Xin; Wang, Lei
In cyber-physical system, computing unit and physical process are usually integrated deeply. This brings great difficulty for modelling cyber-physical system and verifying its properties. We propose algebra of events (AOE) to describe the process of composite events in complex event process. Then, we present an extended hybrid automata based on AOE. It can describe the transition among several states through actuator in CPS better. At last, we model the lunar rover by the extended hybrid automata. The simulation based on this model is introduced to verify the correctness and performance. Simulation result shows that the lunar rover can walk autonomously and safely.